The Development of an Electrochemical Immunosensor Using Chicken Egg Yolk Antibody as a Biological Recognition Element for Detecting Newcastle Disease Virus - Luyen, Tran Thi; Thinh, Tran Quang; Hoang, Tran Vinh; Mai, Nguyen Thi Tuyet; Tuan, Mai Anh; Tuan, Mai Anh (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 2DO - 10.25073/2588-1140/vnunst.4742, 2018)
In this work, the three-electrode system using a quasi-reference Ag/AgCl electrodewas integrated with a microchamber.The chicken egg yolk antibodies (IgY) against Newcastle Disease 68 T.T. Luyến và nnk. / Tạp chí Khoa học ĐHQGHN: Khoa học Tự nhiên và Công nghệ, Tập 34, Số 2 (2018) 62-68 virusNDV used as the biological recognition element was immobilized successfully onthe immunosensor surfaceto replace purified IgG antibody with the complex process of extraction.The electrochemical immunosensor integrated with the microchamber was tested to detect Newcastle disease virus using Cyclic Voltammetry (CV) method. Initial test results showed that the immunosensor has a relatively good and specific response to Newcastle Disease virus. Keywords Electrochemical immunosensor, IgY antibody, Newcastle Disease virus (NDV) References [1] Phạm Văn Ty (2004) Virus học. Nhà xuất bản giáo dục. [2] B. C. Heinze (2010) Lab-on-a-Chip Optical Immunosensor for Pathogen Detection. The University of Arizona. [3] J. Heo, S. Z. Hua (2009) An overview of recent strategies in pathogen sensing. Sensors, vol. 9, pp. 4483–4502. [4] O. Lazcka, F. J. Del Campo, and F. X. Munoz (2007) Pathogen detection: A perspective of traditional methods and biosensors. Biosensors and Bioelectronics, vol. 22, pp. 1205–1217. [5] J. R. North (1985) Immunosensors: Antibody-based biosensors. Trends in Biotechnology, vol. 3, pp. 180–186. [6] S. Thobhani, S. Attree, R. Boyd, N. Kumarswami, J. Noble, M. Szymanski, R. A. Porter (2010) Bioconjugation and characterisation of gold colloid-labelled proteins. Journal of Immunological Methods, vol. 356, pp. 60–69. [7] B. Byrne, E. Stack, N. Gilmartin, R. O’Kennedy (2009) Antibody-based sensors: Principles, problems and potential for detection of pathogens and associated toxins. Sensors (Switzerland), vol. 9, pp. 4407–4445. [8] C. Ding, H. Li, K. Hu, J.-M. Lin (2010) Electrochemical immunoassay of hepatitis B surface antigen by the amplification of gold nanoparticles based on the nanoporous gold electrode. Talanta, vol. 80, pp. 1385–1391. [9] R. Wang, Y. Wang, K. Lassiter, Y. Li, B. Hargis, S. Tung, L. Berghman, W. Bottje (2009) Interdigitated array microelectrode based impedance immunosensor for detection of avian influenza virus H5N1. Talanta, vol. 79, pp. 159–164. [10] M. Page, R. Thorpe (2002) Purification of IgG Using Protein A or Protein G. The Protein Protocols Handbook, 2nd Edition, Humana Press Inc., pp. 993–994. [11] P. J. Conroy, S. Hearty, P. Leonard, R. J. O’Kennedy (2009) Antibody production, design and use for biosensor-based applications. Seminars in Cell and Developmental Biology, vol. 20. pp. 10–26. [12] K. E. Jones, N. G. Patel, M. a Levy, A. Storeygard, D. Balk, J. L. Gittleman, P. Daszak (2008) Global trends in emerging infectious diseases. Nature, vol. 451, pp. 990–993.